Análise Geohistórica da Retirada da Laguna: principais fatores de influência na produção do Espaço - Eduardo Henrique de Oliveira Lima (2023)
The aim of this paper is to analyze geohistorical aspects of the Retirada da Laguna to understand how the environment, the weather and the diseases that affected the troops had an impact on the decisions made in the war, based on the identification of elements produced in Space. Regarding the theoretical and methodological aspects, the geographical categories adopted were discussed. Lefebvrian Space, in its three dimensions (conceived, perceived and lived) is evidence of the peculiar spatial production that took place from/through the Retreat. The history of lives is written/inscribed in lived Space. From this brutally lived Space, the Territory of Mato Grosso do Sul was built. The territorial formation of Mato Grosso do Sul has intense spatial production at its core. The imagery perspective allows this context to be highlighted. The use of imagery favors the understanding of the content and the apprehension of the concepts presented. All because of the possibility of visualizing the entire conceptual arrangement. The hypothetical-deductive method was used to develop the research. The results and discussion described the physical and natural aspects of the route taken, such as: Geology; Geomorphology; Pedology; Topography; Hydrography; Phytophysiognomy; Climatology. The genesis, evolution and consolidation of Mato Grosso was another point discussed. From the Monções in the colonial period, through the introduction of cattle ranching, the creation of the Captaincy to the arrival of the pioneers. The current socio-economic configuration of Mato Grosso, in turn, bears strong traces of its more remote origins. This work analyzes: how the inhospitable environment faced (terrain) decisively influenced the controversial decisions that were made; how the inclement weather limited the advance of the troops; and to what extent the movement of the troops contributed to the spread of diseases, especially cholera, wherever they went. In this way, the study has made the following contributions: a discussion about the production of Space in the Territory of the Retirada; an unprecedented focus on the warlike event that marked all the peoples and nations of the Platine Islands, the memory of which has permeated the regional imagination for over one hundred and fifty years; a demonstration that in addition to Cholera, other diseases made up the health chaos in the southern region of the Province of Mato Grosso; a demonstration of the synergy between lived Space and Territory.